Two-photon imaging of Zn(2+) dynamics in mossy fiber boutons of adult hippocampal slices - Khan, Mustafa (National Academy of Sciences, 2014)
Mossy fiber termini in the hippocampus accumulate Zn(2+), which is released with glutamate from synaptic vesicles upon neural excitation. Understanding the spatiotemporal regulation of mobile Zn(2+) at the synaptic level is challenging owing to the difficulty of visualizing Zn(2+) at individual synapses. Here we describe the use of zinc-responsive fluorescent probes together with two-photon microscopy to image Zn(2+) dynamics mediated by NMDA receptor-dependent long-term potentiation induction at single mossy fiber termini of dentate gyrus neurons in adult mouse hippocampal slices. The membrane-impermeant fluorescent Zn(2+) probe, 6-CO(2)H-ZAP4, was loaded into presynaptic vesicles in hippocampal mossy fiber termini upon KCl-induced depolarization, which triggers subsequent endocytosis and vesicular restoration. Local tetanic stimulation decreased the Zn(2+) signal observed at individual presynaptic sites, indicating release of the Zn(2+) from vesicles in synaptic potentiation. This synapse-level two-photon Zn(2+) imaging method enables monitoring of presynaptic Zn(2+) dynamics for improving the understanding of physiological roles of mobile Zn(2+) in regular and aberrant neurologic function.